Analysis of Technological Pedagogical And Content Knowledge Teachers physics Overcoming Misconceptions Newton's Law - Halim, A; Rizki, Meisy Adha (STKIP Singkawang, 2024)
Misconceptions in students must be corrected immediately so that there is no retention of misconceptions in subsequent knowledge. One way to prevent and reduce misconceptions that occur in students is with the ability of Technological Pedagogical and Content Knowledge (TPACK) of teachers. Teachers who integrate TPACK in learning can prevent misconceptions and find solutions to overcome the misconceptions that occur. This study aims to determine the TPACK ability of teachers in overcoming misconceptions,. The research method used in this study is a Mixed method with an unbalanced mixed research design (Concurrent Embedded design). The results showed that the teacher's TPACK ability can improve students' concept understanding. This is indicated by the N-Gain score= 0.72, which means that the teacher's TPACK ability is effective in improving concept understanding on newton's law material.